RAMA-WeRA Risk Score in Predicting the Ruptured Appendicitis in Emergency Department; a Multicenter Study for External Validation - Tienpratarn, Welawat; Kasemlawan, Guyphol; Yuksen, Chaiyaporn; Kongchok, Wanchalerm; Boonyok, Nitchakarn; Lowanitchai, Piyanuch; Boriboon, Jeeranun; Rattananikom, Thidarat; Phootothum, Yuranun; Jaiboon, Sutap (Archives of Academic Emergency Medicine, 2024)
Introduction: Distinguishing between ruptured and non-ruptured acute appendicitis presents a significant challenge. This study aimed to validate the accuracy of RAMA-WeRA Risk Score in predicting ruptured appendicitis (RA) in emergency department. Methods: This study was a multicenter diagnostic accuracy study conducted across six hospitals in Thailand from February 1, 2022, to January 20, 2023. The eligibility criteria included individuals aged >15 years suspected of acute appendicitis, presenting to the ED, and having an available pathology report following appendectomy or intraoperative diagnosis by the surgeon. We assessed the screening performance characteristics of RAMA-WeRA Risk Score, in detecting the ruptured appendicitis (RA) cases. Results: 860 patients met the study criteria. 168 (19.38%) had RA and 692 (80.62%) patients had non-RA. The area under the receiver operating characteristic curve (AuROC) of RAMA-WeRA Risk Score was 75.11% (95% CI: 71.10, 79.11). The RAMA-WeRA Risk Score > 6 points (high-risk group) demonstrated a positive likelihood ratio (LR) of 3.22 in detecting the ruptured cases. The sensitivity and specificity of score in > 6 cutoff point was 43.8% (95%CI: 36.2, 51.6) and 86.4% (95%CI: 83.6, 88.9), respectively. Conclusions: The RAMA-WeRA Risk Score can predict rupture in patients presenting with suspected acute appendicitis in the emergency department with total accuracy of 75% for high-risk cases.